(untitled) (University Journal of Zoology, Rajshahi University, 2007)
Key words: Baluhar Baor area; amphibian; reptilian; avian and mamalian fauna; abundance Univ. j. zool. Rajshahi Univ. Vol.22, 2003. pp.131-136